(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Leadership can be defined in different ways that it is hard to come up with a single working definition. Leadership is not just a person or group of people in a high position. Leadership is a process in which leader is indulged in various activities to achieve any goal. Leadership refers to the behaviour / attitude of a leader to collect and direct the individuals towards any goal. Leadership is a communication process of leader and individuals. So the effectiveness of an organization depends upon the effective leader and effective leader is that person who has an effective leadership style. Leadership is a very important factor for any organization or group.